Studies in Aegean art and culture : a New York Aegean Bronze Age Colloquium in Memory of Ellen N. Davis - Davis, Ellen N.; Koehl, Robert B.; Koehl, Robert B. (INSTAP Academic Press, 2016)
1.The silver kantharos from Gournia revisited /Judith Weingarten --2.Helladic pairs of cups /Malcolm H. Wiener --3.For Ellen Davis : Transylvanian gold/Gunter Kopcke --4.Cycladic and more northerly connections in the metal objects from Petras Cemetery /James D. Muhly --5.The human condition as reflected in early Aegean art /Christos Doumas --6.Purple rosettes/Σoρφυρoι ρoδακεσ : new data on polychromy and perception in the Thera wall paintings /Andreas G. Vlachopoulos --7.Depictions of water in Aegean miniature-style wall paintings /Elizabeth B. Shank --8.The three Minoan "snake goddesses" /Bernice R. Jones --9.Beyond the "chieftain cup" : more images relating to Minoan male "rites of passage" /Robert B. Koehl --10.. The ideology of the ruler in Mycenaean prehistory : twenty years after the missing ruler /Thomas G. Palaima.